Knowledge about Acute Respiratory Infection and Home Care Practice among Mothers of Under Five Years Children in Hima Rural Municipality, Jumla, Nepal - Bishal Pokhrel,; Gauri Bahadur Rokaya,; Kriti Parajuli,; Binata Pokhrel Subedi, (Janaki Medical College Journal of Medical Science, 2023)
Background and Objectives: Acute Respiratory Infection (ARI) is defined as acute infective inflammatory changes in any part of respiratory tract, from the nasal mucosa to the alveoli, with an alteration in the respiratory physiology. ARI is a leading causes of mortality and morbidity in under-five children worldwide. This study aimed to assess knowledge about acute respiratory infection and home care practice among mothers of under-five year’s children and to determine the factors associated with it among mothers of under five children in Hima Rural Municipality, Jumla. Materials and Methods: The community based cross sectional study was conducted. Data was collected using systematic random sampling technique method and face to face interview was conducted using pretested semi-structured questionnaire. Data entry was used Epi-data 4.6 version and analyzed by using SPSS 20.0 version. Results: About 94.9% of the participant’s mother had heard about the ARI and 24.9% participant’s mother had high level of knowledge about ARI. 70.8% participants keep the child in a room with window and door close the room warm. As prevention and control highest percentage of the participants mothers 61.1% preferred to give Tito leaf tea. 59.1% mother were breast feeding than frequently to their ARI babies. Conclusion: The most of the women had knowledge about ARI. More than half of mothers preferred health facility for neighbor child as a choice of treatment. Most of the mothers kept their child in a room with window and door closed to keep the room warm. More than half reduce fever by cold sponge and wrap the child with tight and thick when child had ARI. Most of the ARI cases were treated at home and cured. Among total participants less than half followed health post after not cured at home.